Developing an understanding of canine adoption and how owner experience impacts on success - Clark, Gemma Louise (2015)
In 2010 in the United Kingdom an estimated 89,571 dogs passed through re-homing centres (Stavisky et al. 2012). Around 50% of these were relinquished by owners, with the rest largely being strays. Reasons for relinquishment have been widely reported. After adoption, the percentage of dogs being returned to re-homing centres (re-relinquishment) has been reported between 0% and 26% across a cross section of United Kingdom organisations (King, 2010). To date, research considering the success of canine adoption has been mostly retrospective and relatively limited in scope. The aim of this study was to investigate owner’s experience of adoption as they are the decision makers who ultimately control the outcome.